PELAKSANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SMP IT IZZUDDIN PALEMBANG - Thoyyibah Tulillah (UNISAN JURNAL, 2023)
The formulation of the problems in this study are (1) How is the planning of the principal’s academic supervision program in improving teacher performance at SMP Ma’arif 03 Labuhan Maringgai?, (2) How is the implementation of the principal’s academic supervision program in improving teacher performance at SMPIT Izzuddin Palembang?, (3) How is the follow-up to the principal’s academic supervision program in improving teacher performance at SMPIT Izzuddin Palembang?. This research is qualitative in nature because it seeks to reveal the symptoms of a particular tradition that fundamentally depends on human observation in its discussion and terminology. The results of the study found that (1) In planning the supervision program, the principal has done the planning well, but there are still shortcomings. This is known from the data which shows that the supervision program is planned 2 times a year. (2).In the implementation of the supervision program, the principal has carried out classroom visits according to the schedule, however, in providing guidance on making learning tools it is not optimal. (3) In the follow-up of supervision, principals do not analyze the findings of supervision. Principals also do not conduct feedback findings as reinforcement after supervision. Therefore, the follow-up supervision is not optimal.